Erythrocyte membrane-coated gold nanocages for targeted photothermal and chemical cancer therapy. (17th January 2018) - Zhu, Dao-Ming; Xie, Wei; Xiao, Yu-Sha; Suo, Meng; Zan, Ming-Hui; Liao, Qing-Quan; Hu, Xue-Jia; Chen, Li-Ben; Chen, Bei; Wu, Wen-Tao; Ji, Li-Wei; Huang, Hui-Ming; et al.
Abstract: Recently, red blood cell (RBC) membrane-coated nanoparticles have attracted much attention because of their excellent immune escapability; meanwhile, gold nanocages (AuNs) have been extensively used for cancer therapy due to their photothermal effect and drug delivery capability. The combination of the RBC membrane coating and AuNs may provide an effective approach for targeted cancer therapy. However, few reports have shown the utilization of combining these two technologies. Here, we design erythrocyte membrane-coated gold nanocages for targeted photothermal and chemical cancer therapy. First, anti-EpCam antibodies were used to modify the RBC membranes to target 4T1 cancer cells. Second, the antitumor drug paclitaxel (PTX) was encapsulated into AuNs. Then, the AuNs were coated with the modified RBC membranes. These new nanoparticles were termed EpCam–RPAuNs. We characterized the capability of the EpCam–RPAuNs for selective tumor targeting via exposure to near-infrared irradiation. The experimental results demonstrate that EpCam–RPAuNs can effectively generate hyperthermia and precisely deliver the antitumor drug PTX to targeted cells. We also validated the biocompatibility of the EpCam–RAuNs in vitro . By combining the molecularly modified targeting RBC membrane and AuNs, our approach provides a new way to design biomimetic nanoparticles to enhance the surface functionality of nanoparticles. We believe that EpCam–RPAuNs can be potentially applied for cancer diagnoses and therapies.